2022
DOI: 10.3390/cancers14010261
|View full text |Cite
|
Sign up to set email alerts
|

Association between CT-Based Preoperative Sarcopenia and Outcomes in Patients That Underwent Liver Resections

Abstract: This retrospective observational study aimed to evaluate whether preoperative sarcopenia, assessed by CT imaging, was associated with postoperative clinical outcomes and overall survival in patients that underwent liver resections. Patients operated on between January 2014 and February 2020 were included. The skeletal muscle index (SMI) was measured at the level of the third lumbar vertebra on preoperative CT scans. Preoperative sarcopenia was defined based on pre-established SMI cut-off values. The outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…Indications to surgery consisted in CRLM (43.7%), HCC (13.2%), CCA (15.5%); 10% of the patients underwent surgery for non-oncological indications. The authors concluded that other items like muscle strength and physical performance, in addition to imaging, should be considered for preoperative risk stratification ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indications to surgery consisted in CRLM (43.7%), HCC (13.2%), CCA (15.5%); 10% of the patients underwent surgery for non-oncological indications. The authors concluded that other items like muscle strength and physical performance, in addition to imaging, should be considered for preoperative risk stratification ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, whether a minimally invasive approach (MILS) for oncologic liver resection could reduce the impact of an unfavorable body composition profile by reducing for example abdominal wall trauma has not been specifically addressed. The rate of MILS adoption in the studies included is scarcely reported (seven out of 33 articles included) and subgroup outcomes have been reported in only two studies without significant findings ( 16 , 17 ). This indeed would represent an interesting field of research.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While there are only a few publications dealing with sarcopenia as a predictor of kidney graft outcome [5,16,19,20,30,31], a large number of studies published in the last years show an increased postoperative morbidity and mortality after visceral surgery and in oncologic patients [37][38][39][40][41][42][43]. A meta-analysis explored independent risk factors for [45].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of sarcopenia did not differ significantly between primary hepatic malignancies and metastases. Of the studies combining different malignancies [30,32,49], two did not refer to SMI as a measure of sarcopenia alone, but Berardi et al used the combination of reduced muscle mass and strength as a definition of LSMM, while Valero et al applied TPA and TPV. Our overall results exhibit a somewhat lower OR for post-operative complications for liver resection than those published for gastrectomy or surgery for CRC [13,14].…”
Section: Discussionmentioning
confidence: 99%